Midshaft Clavicle Fractures: Surgery Provides Better Results as Compared With Nonoperative Treatment: A Meta-analysis. Issue 14 (December 2019) - Guerra, Enrico; Previtali, Davide; Tamborini, Simone; Filardo, Giuseppe; Zaffagnini, Stefano; Candrian, Christian
Background: There is no agreement on the best treatment for displaced midshaft clavicle fractures (MCFs), which are currently addressed by nonoperative or surgical approaches. Purpose: To compare fracture healing and functional outcome after surgical versus nonsurgical treatment of MCFs, to help specialists in deciding between these different strategies by providing a synthesis of the best literature evidence. Study Design: Meta-analysis. Methods: A systematic research of the literature was performed in different online databases: PubMed, Web of Science, Cochrane library, and grey literature. PRISMA (Preferred Reporting Items for Systematic Meta-Analyses) guidelines were used. The risk of bias was evaluated with the Cochrane Collaboration's "risk of bias" tool, and the quality of evidence was graded according to Grading of Recommendations Assessment, Development and Evaluation (GRADE) guidelines. Randomized controlled trials investigating differences between surgery and nonoperative treatment for displaced MCFs were included. The primary outcome was the nonunion rate. Other outcomes analyzed were time to union and to return to activities, Constant score, and Disabilities of the Arm, Shoulder and Hand (DASH) index. Patients' satisfaction, secondary operations, and complications were also recorded. Results: Out of 832 records found, 14 randomized controlled trials with 1546 patients were included. A significantly lower risk ratio was found for nonunion (10%; 95% CI, 6%-18%, P < .001) favoring surgery. Time to union was 5.1 weeks shorter with surgery ( P = .007). The complication rate (including the number of reinterventions) was higher in the surgical group (31.3% vs 20.5%, P < .001). Shoulder function at short-term follow-up was significantly better in the surgical group (DASH index mean difference = 4.0 points), while no statistical difference was found in the Constant score and in the DASH index at midterm follow-up ( P = .41 and .80, respectively). At long-term follow-up, both shoulder functional scores were significantly better in the surgery group: the overall Constant score mean difference was 5.3 points (95% CI, 2.3-8.4 points; P < .001), and the DASH index mean difference was 4.3 points (95% CI, 0.2-8.4 points; P = .04). Conclusion: Surgical treatment of MCFs significantly reduces the nonunion rate and shortens the time to union as compared with the nonoperative approach and, despite a slightly higher incidence of complications, leads to better shoulder functional scores at short- and long-term follow-up. Further studies should address the clinical significance of the documented improvement.